Factors influencing infertility-related quality of life in infertile women - Yun Mi Kim; Ju-Hee Nho (Korean Society of Women Health Nursing, 2020)
Purpose Infertile women experience various physical, psychological, and relational problems that affect their infertility-related quality of life (QoL). This study investigated infertile women's infertility-related QoL with the goal of identifying how it is influenced by fatigue, depression, and marital intimacy. Methods A sample of 140 infertile women was surveyed in a cross-sectional study. Data were collected from February to April 2018 using self-report structured questionnaires at three infertility clinics located in Jeonju, Korea. Data were analyzed using the independent t-test, analysis of variance, Pearson correlation coefficients, and stepwise multiple regression analysis in SPSS for Windows version 25.0. The subjects agreed to complete a face-to-face interview, including administration of the Fatigue Severity Scale, Depression Anxiety Stress Scale-21, Marital Intimacy Scale, and the Fertility Quality of Life tool. Results The mean age of the participants was 35.6±4.3 years. Infertility-related QoL was negatively correlated with fatigue (r=-.42, p<.001) and depression (r=-.56, p<.001), and positively correlated with marital intimacy (r=.30, p<.001). Multiple regression analysis showed that depression (β=-0.44, p<.001), fatigue (β=-0.27, p<.001), and husband's attitude (β=-0.19, p=.007) had significant effects on the QoL of infertile women, accounting for 40.5% of the variance in infertility-related QoL. Conclusion The study provides insights into how infertile women's infertility-related QoL was influenced by depression, fatigue, and their husbands' attitudes regarding infertility treatment. To improve infertile women's infertility-related QoL, healthcare providers should consider developing strategies to decrease depression and fatigue in infertile women and to address their husbands' attitudes.